Dampak Profitabilitas, Ukuran Perusahaan, Struktur Modal, Keputusan Investasi Terhadap Nilai Perusahaan - Jayanti, Inti Dwi (BISMA : Business and Management Journal, 2024)
The value of companies in the consumer product manufacturing industry listed on the Indonesian Stock Exchange during 2020 and 2022 will be studied to determine the influence of capital structure, choices regarding investments, profitability, and company size. A total of 36 firms were chosen for the purpose of sampling using a purposive sampling approach. We used the technique of multiple linear regression analysis to see if our idea held water. Profitability and investment decisions, in contrast to business size and structure of capital, are shown to have a positive and statistically significant effect on firm value. Company size and structure of capital are not major factors in determining profitability; rather, high profitability is an indication of effective profit generation by management. High profitability reflects management efficiency in generating profits, while appropriate investment decisions indicate long-term growth potential, both contributing to increased firm value. These findings highlight the importance of effective management in maintaining profitability and making strategic investment decisions to maximize firm value. This research provides valuable insights for financial managers and investors in understanding the factors that influence firm value in the consumer goods manufacturing sector.